Nature of the Universe: Astrophysical Paradigm Shifts - Herndon, J. Marvin (Advances in Social Sciences Research Journal, 2021)
Over my lifetime I have witnessed the decline of scientific capability and integrity in the physical sciences. When a new idea arises, it should be discussed and debated. Attempts should be made to refute the new idea; otherwise, it should be cited in subsequent literature. That is the way science progresses, not by attempting to suppress a new idea or failing that, to ignore it. But all too often, in instances of discoveries or insights that might cause major paradigm shifts, suppression or non-recognition is what happens. Here, I describe, from a first-person perspective, several paradigm shifts in astrophysics that have been systematically ignored, including the thermonuclear ignition of stars, the nature of dark matter, why vast numbers of galaxies have just a few prominent patterns of luminous stars, the origin of chemical elements, and a new speculation about the nature of the Universe.